RELEVANSI PERAN PANGKALAN TNI ANGKATAN LAUT TERHADAP TERWUJUDNYA WILAYAH PERTAHANAN YANG BERTUMPU PADA PULAU-PULAU BESAR (STUDI KASUS PADA LANTAMAL III/JAKARTA) - Endra Kusuma; Syaiful Anwar; Helda Risman; Ruslan Arief (Jurnal Inovasi Penelitian, 2021)
The Main Naval Base III Jakarta as a regional command unit has a role in preparing formidable space, tools and fighting conditions by empowering marine defense areas through fostering maritime potential (binpotmar) as part of the Archipelago Marine Defense Strategy (SPLN). In its implementation, national defense at sea must follow the defense policy set by the state. Currently, the government has ratified the general policy of state defense for 2020-2024 with one of the policy targets being the realization of a defense area based on large islands. With the determination of this national defense policy, it is necessary to synchronize the SPLN that has been carried out by the Navy with one of the strategic objectives of the policy. The purpose of this study is to determine the relationship between the empowerment of the marine defense area through BinPotmar and elements in an effort to realize a defense area based on large islands. This study uses a qualitative research method with a Grunded Theory approach using relevance theory, role theory, coaching theory, Sea Power theory and logistics theory. The results of the study conclude that the empowerment of marine defense areas through binpotmar has relevance to the realization of defense areas that rely on large islands.